Effect of the transitional care program on readiness for hospital discharge and activities of daily living among older patients with open heart surgery - Somanawat, Chuthamat; Leethong-in, Mayuree; Mitprachapranee, Chalach (Journal of Medicine and Health Sciences, 2023)
Open heart surgery among older adults were different from other ages, due to the characteristics of the elderly with complex long-term surgery and affected the recovery postoperative period. If the older patients had insufficient readiness, it will affect self-care when hospitals discharge these patients to their homes. The purpose of this quasi-experimental research design, after-only experimental with a control group, was to investigate the effects of a transitional care program on the readiness for hospital discharge and the activities of daily living among older patients with open heart surgery. Weiss’ readiness for hospital discharge concept and the nursing therapeutic factors of Meleis’ transition theory were also applied. Older patients undergoing open heart surgery for the first time at Srinagarind Hospital, Khon Kaen were recruited. The study was conducted from January to March 2023. A control group of 15 patients received normal care while 15 patients in the experimental group received developed a transitional care program, which operated in two phases: the preoperative phase (preparation before surgery) and the postoperative period (rehabilitation and practice during the recovery period at home). The content validity index (CVI) was checked by experts, and was found to be at 1.00. The data collection instruments consisted of a general information questionnaire, the Readiness for Hospital Discharge Scale and Barthel ADL Index. The data were analyzed using descriptive statistics, an independent t-test and a Mann-Whitney U test. The results showed that the mean scores of readiness for hospital discharge of the older patients with open heart surgery in the experimental group after receiving the transitional care program were significantly higher than that of the control group receiving normal care (t = 6.679, p<0.001). Also, the median score of activities of daily living, two weeks after hospital discharge was significantly higher than the control group (Mann-Whitney U = 36.50, p<0.001). In conclusion, this transitional care program was effective. It can increase the readiness for hospital discharge and daily activities after hospital discharge.